Research of running contacts wear based on simulation of current distribution in the pantograph slide - D. V. Tartynsky; M. N. Yemelyanova; A. T. Tibilov (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
In order to solve the task related to wear reduction in the current shoe insert the authors defined the processes which have a bearing on their operation. In order to analyze interactions between the components of the current collection system the authors considered a physical analogue for current distribution from the catenary contact wire to the inserts of the pantograph slide mounted on the electrically propelled vehicles - EMUs. In that model the sliding contact point moves along the strip on the both sides of the axis of symmetry at a speed which is proportional to EMU speed. The current collection process was simulated as an equivalent circuit where the current flows through variable resistors according to the sliding contact position and further on through fixed resistors corresponding to points of bypass wires fixture on the pantograph slide. The equivalent circuit was developed with the following allowances: continuous current collection is expected; transition resistances between the inserts and the contact wire and also between the inserts and the copper underlay of the pantograph slide are neglected; the contact wire is always at right angle to the row of inserts (zigzag is ignored). Calculations made for the equivalent circuit have shown that the central part of pantograph slide is overheated with the current flow through the inserts. For this reason there was suggested a hypothesis that the inserts wear rate produced by the pantograph slide heating should be higher in the central part than on the periphery. References to theoretical and experimental researches have shown that existing pantograph slide designs fail to secure economic use of current collection materials. In the light of their own research the authors suggest that there should be developed new designs of pantograph slide in which the maximum heating in the central part would be lowered.